The Influence of Management Decisions on the Capital Structure Optimization of Ukrainian Agricultural Enterprises - Lemishko, О. О.; Blazhevich, А. М. (Statistics of Ukraine, 2022)
The article defines the influence of management decisions on the capital structure optimization. A statistical analysis of the dynamics and capital structure of Ukrainian agricultural enterprises for 2016–2020 is presented. It is established that effective capital management is aimed at forming its optimal structure. Based on the capital functioning diagnostics, it is determined that despite the increase in the share of the agricultural enterprises’ equity capital in the total capital, the profitability of equity capital decreased significantly. This proves, among other things, ineffective management of the agricultural enterprises’ capital structure. It is shown that increasing the profitability of not only the total capital, but also each of its components (own capital, borrowed capital), is the main indicator of the capital structure optimization, and, accordingly, of the management decision-making appropriateness. It is substantiated that the enterprise’s efficiency activity is determined by the functioning of its capital, and the correctly chosen capital management enterprise’s strategy allows ensuring financial stability and high profitability indicators. It is proven that an effective system of managing the agricultural enterprises’ capital structure is subject to the definition of the hierarchy and sequence of capital management levels. It is established that at the strategic level of capital management, it is very important to define the tools for developing the chosen management strategy, taking into account the specifics of agricultural production; the implementation of capital management tactics is subordinated to the stabilization of the agricultural enterprises’ resource base, including through the marketing policy formation and enterprise policy on the financial market. It is substantiated that operational management decisions are aimed at optimizing the level of financial risk associated with attracting loan funds and increasing their share in the structure of the agricultural enterprises’ aggregate capital.